Itraconazole induces apoptosis and cell cycle arrest via inhibiting Hedgehog signaling in gastric cancer cells - Hu, Qiang (J Exp Clin Cancer Res, 2017)
BACKGROUND: Itraconazole has been proved therapeutically effective against a variety of human cancers. This study assessed the effect of itraconazole on the Hedgehog (Hh) pathway and proliferation of human gastric cancer cells. METHODS: CCK-8 assay and colony formation assay were used to assess the effects of itraconazole on proliferation of gastric cancer cells. The expression of Hh signaling components in gastric cancer cells treated with itraconazole was evaluated by reverse-transcription polymerase chain reaction, immunoblotting and dual luciferase assay. Tumor xenograft models were used to assess the inhibitory effect of itraconazole on the proliferation of gastric cancer cells in vivo. RESULTS: Itraconazole could remarkably inhibit the proliferation of gastric cancer cells. When in combination with 5-FU, itraconazole significantly reduced the proliferation rate of cancer cells. Furthermore, itraconazole could regulate the G(1)-S transition and induce apoptosis of gastric cancer cells. Hh signaling was abnormally activated in human gastric cancer samples. In vitro, studies showed that the expression of glioma-associated zinc finger transcription factor 1 (Gli1) was decreased at both transcriptional and translational levels after treatment with itraconazole. Dual luciferase assay also indicated that itraconazole could inhibit the transcription of Gli1. In vivo studies demonstrated that monotherapy with itraconazole by oral administration could inhibit the growth of xenografts, and that itraconazole could significantly enhance the antitumor efficacy of the chemotherapeutic agent 5-FU. CONCLUSIONS: Hh signaling is activated in gastric tumor and itraconazole can inhibit the growth of gastric cancer cells by inhibiting Gli1 expression.